2004
DOI: 10.1097/01.tp.0000128327.95311.e3
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Controlled, Non—Heart-Beating Donor Liver Transplantation

Abstract: CNHBD safely expands the donor pool with similar long-term results as those obtained in patients receiving organs from brain-dead donors under standard procurement techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(60 citation statements)
references
References 15 publications
6
52
0
2
Order By: Relevance
“…The follow-up is, however, still relatively short and more data are needed on the longerterm outcomes. The encouraging long-term results from Manzarbeitia et al with adult recipients show that the cautious use of NHBD livers produces survivals, which are no different than for those recipients receiving standard heartbeating deceased donor grafts, with a similar incidence of vascular and biliary complications (10).…”
Section: Discussionmentioning
confidence: 84%
“…The follow-up is, however, still relatively short and more data are needed on the longerterm outcomes. The encouraging long-term results from Manzarbeitia et al with adult recipients show that the cautious use of NHBD livers produces survivals, which are no different than for those recipients receiving standard heartbeating deceased donor grafts, with a similar incidence of vascular and biliary complications (10).…”
Section: Discussionmentioning
confidence: 84%
“…Concerns regarding prolonged ischemia time and graft dysfunction have been raised; however, several reports have indicated that renal and liver grafts from DCD donors have graft function and transplant recipient survival rates comparable to those with organs recovered from braindead donors. [15][16][17][18][19] In addition, lungs from DCD donors are now being recovered with good success. 9 The Institute of Medicine and the American College of Critical Care Medicine both endorse DCD as a means to recover organs for transplantation.…”
Section: Organ Donationmentioning
confidence: 99%
“…Increasing DRI has been strongly correlated with decreasing graft and patient survival. While these 'marginal' organs can be successfully used in the proper patient, they are at higher risk of graft dysfunction, graft failure and potentially decreased patient survival (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%